1992
DOI: 10.3102/00028312029002253
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis as a Public Event: The Documentation of Category Development Procedures

Abstract: Although the use of qualitative methods has increased greatly in popularity, many still question the defensibility of the qualitative orientation. It is argued here that questions concerning the credibility and status of qualitative inquiry are related to the privatization of qualitative analysis. The particular area of qualitative analysis I focus on is the process of category development. It is my argument that qualitative researchers must make all aspects of their analysis open to public inspection. In orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
155
0
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(160 citation statements)
references
References 0 publications
0
155
0
5
Order By: Relevance
“…The locus of typology development was investigative, arising from the intellectual constructions of the researchers (Constas, 1992). The sources for naming codes and locus of typology (i.e., theme) development were literature (i.e., based on Ramirez et al's (2010) reframing of the EVM) and investigative (i.e., stemming from the intellectual constructions of the researchers (Constas, 1992)) within an iterative process involving both a priori and a posteriori coding. More specifically, abductive coding was used that involved an interactive process of deductive coding and inductive coding.…”
Section: Qualitative Analysesmentioning
confidence: 99%
See 3 more Smart Citations
“…The locus of typology development was investigative, arising from the intellectual constructions of the researchers (Constas, 1992). The sources for naming codes and locus of typology (i.e., theme) development were literature (i.e., based on Ramirez et al's (2010) reframing of the EVM) and investigative (i.e., stemming from the intellectual constructions of the researchers (Constas, 1992)) within an iterative process involving both a priori and a posteriori coding. More specifically, abductive coding was used that involved an interactive process of deductive coding and inductive coding.…”
Section: Qualitative Analysesmentioning
confidence: 99%
“…The extracted themes were compared to the quantitative information-namely, the CSIS scores and quantitative demographic information (e.g., number of prior mathematics courses)-to assess levels of triangulation. Because quantitative data were used as a validation technique, in addition to being empirical the verification component of categorization was technical (Constas, 1992). The verification approach was accomplished a posteriori (Constas, 1992).…”
Section: Qualitative Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Existing documentary and archival material was also gathered to supplement the interview data and to provide some triangulation of observations. Data gathered from interviews and questionnaires were then analysed using thematic analysis, so that qualitative data collected from participants and quantitative data collated from other sources could be integrated more effectively (Boyatzis 1998;Constas, 1992;Dixon-Woods, Agarwal, Jones, Young and Sutton 2005). The themes which formed the basis for this analysis were primarily those of the overall study's theoretical framework (reported in Ridley (2006)) and are therefore not specifically related to the UniSA environment, but rather designed to provide comparability across States within a national study.…”
Section: Research Approachmentioning
confidence: 99%